Andrew Parkinson, Jonathon Green: Cutting it Fine. Inside the Restaurant Business - Jaine, Tom (Petits Propos Culinaires, 2024)
Andrew Parkinson, Jonathon Green: Cutting it Fine. Inside the Restaurant Business: Jonathan Cape, London, 2001: ISBN 0-224-06077-5: 308 pp., many b/w photos, p/b, £14.99.